Digital technologies in forced virtuality and its implications in the training of teachers in Mathematics (Itinerarios Educativos, 2025)
In this paper we present the results of an interpretive–descriptive research. We analyzed the teaching proposals of students who took the Teaching Practice in contexts of forced virtuality (2020–2021) in the Mathematics Teaching career at UNL. We explain how TD were included in the secondary school classroom. We study the types and purposes of use of digital resources and identify aspects considered valuable by practitioners to teach mathematics mediated by them. We recognized epochal traits in their voices that contribute to the design of proposals in the new in–person scenarios.
Keywords: Digital technology; mathematics education; virtuality; teaching practice